Assessing the Use of Limestone With Expanded Clay Aggregates in Water Treatment - Gerald kubaLo (Uganda Christian University, 2025)
This research aimed to assess the use and efficiency of limestone with expanded clay aggregates in Nyaruzinga Treatment Plant in Bushenyi. The water is abstracted from Nyaruzinga wetland which is a Cyperus papyrus wetland with high biomass. The physiochemical characteristics of the raw water source were determined in both wet season and dry season. There was a high variation of iron in the water of (11±1 mg/l) with respect to the WHO standards. This variation was corresponding to the levels of turbidity (5.18-6.16), colour (522±2 PtCo), electrical conductivity (84.6±2.52) and pH of the water as parameters of interest. The cascade aeration technique applied at the treatment plant reduced the iron concentration to a less value (3.72±0.14 mg/l). However, the final treated water contained a significant variation of iron (Kanyesigye et al,2023). Limestone sourced from Kabaale was crushed into powder and passed through 45µm sieve. A batch test provided the optimum dosage of 3g/l at pH 8 required to precipitate out the iron ions as iron (iii) carbonate. The expanded clay aggregates made from clay and fired to 1100 °C were used in a filtration column to sieve out the precipitate and residue. The introduction of limestone into the coagulation process provided a (94.17%) drop in the iron concentration and the expanded clay aggregates reduced the TDS after the filtration
Undergraduate